Pengambangan Media Pembelajaran Interaktf Berbasisi QuizWhizzer Untuk Meningkatkan Pemahaman Konsep Dan Partisipasi Siswa Sekolah Dasar - Wardatun Laela; Liyana Sunanto (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study aims to examine in depth the effectiveness of interactive learning media based on QuizWhizzer in improving students' conceptual understanding and participation in Mathematics subjects in elementary schools. The background of this study is the problem of low student engagement and difficulties in understanding mathematical concepts due to conventional learning methods. The research method used is a literature review by reviewing 30 scientific articles from national and international journals relevant to the topic of interactive media and mathematics learning. The results of the study indicate that the application of interactive game-based learning media such as QuizWhizzer can increase learning motivation, student engagement, and strengthen the understanding of mathematical concepts through fun and competitive quiz activities. This media also supports the game-based learning approach and the theory of cognitivism that emphasizes the active role of students in constructing knowledge. In conclusion, QuizWhizzer is an effective and feasible innovative alternative for mathematics learning in elementary schools to create an active, meaningful, and interactive learning atmosphere.